Filter for purifying plating solution and adsorbent for purifying plating solution
By using filters and adsorbents for purification of the plating solution formed by activated carbon, the characteristics of their molded bodies are adjusted, and the problems of uneven plating and chlorine dissolution in the acid copper foil plating solution are solved, thereby achieving efficient decomposition product removal and improving the quality of the plating solution.
Patent Information
- Application Number
- CN201980086060.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-27
- Filing Date
- 2019-12-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2039-12-24
AI Technical Summary
In the acidic copper foil plating solution, after using an activated carbon-containing filter, the quality of the plating solution is prone to deterioration, resulting in uneven plating problems, and high chlorine concentration will lead to the dissolution of the anode metal and the dissolution of chlorine in the activated carbon.
The filter for purification of the plating solution formed by activated carbon is used to adjust the iodine adsorption amount, chloride ion concentration, pH value and conductivity of the molded body to inhibit the removal of additives, efficiently remove decomposition products, and inhibit chlorine dissolution.
It effectively inhibits the removal of additives, efficiently removes decomposition products from the plating solution, and prevents chlorine from dissolution, improves the quality of the plating solution, and ensures the uniformity and quality of the plating layer.
Smart Images

Figure CN113227461B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a filter for purifying a plating solution and an adsorbent for purifying the plating solution. Background Art
[0002] Filters containing activated carbon are widely used not only for water purification but also for liquid purification. For example, Patent Document 1 discloses an activated carbon-containing filter which has alkali resistance and is used for purifying a plating solution.
[0003] On the other hand, in addition to the plating components, various additives are added to the plating solution to improve the plating quality. For example, macromolecular organic compounds such as polyethylene glycol, polyvinyl alcohol, and gelatin are added as additives to the plating solution for electroplating. It is known that the macromolecular organic compound gradually decomposes in the liquid and becomes low molecular decomposition products as impurities whenever electroplating is performed. If the decomposition products increase in the plating solution, the plating quality deteriorates, so it is necessary to remove the decomposition products.
[0004] For example, Patent Document 2 discloses a method of removing decomposition products from a plating solution using a filter containing activated carbon and reusing the plating solution.
[0005] However, according to the investigation by the present inventors, when an acidic copper foil plating solution is used, when plating is performed using a plating solution in which the decomposition products are adsorbed and removed using an activated carbon-containing filter (hereinafter referred to as a "regenerated plating solution"), the plating quality sometimes deteriorates, such as uneven plating.
[0006] The inventors have studied the causes of this quality deterioration and found that if the chlorine concentration in the acidic copper foil plating solution is high, the dissolution of the anode metal and metallic copper into the plating solution is promoted, thereby causing uneven plating and chlorine elution from the activated carbon-containing filter into the regenerated plating solution.
[0007] Furthermore, it was found that when using an activated carbon-containing filter, not only decomposition products but also additives including necessary high-molecular organic compounds are removed from the regenerated plating solution, thereby causing a deterioration in plating quality.
[0008] The present invention is made in view of the above situation, and its purpose is to provide a filter for purifying plating liquid and an activated carbon adsorbent for preparing the filter for purifying plating liquid, which can not only inhibit the removal of additives but also efficiently remove the decomposition products generated by the additives from the plating liquid, and can also inhibit the dissolution of chlorine into the plating liquid.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Publication No. 2012-61390
[0012] Patent Document 2: Japanese Patent Publication No. 2005-240108 Summary of the invention
[0013] The present inventors have conducted various studies and found that the above-mentioned object can be achieved by the following invention.
[0014] A filter for purifying a plating solution according to one aspect of the present invention comprises a molded body containing an adsorbent formed of activated carbon and having an iodine adsorption amount per unit mass of 930 to 1300 mg / g, wherein the chloride ion concentration of filtered water obtained after filtering raw water having a chloride ion concentration of 6.0 to 9.0 mg / L, a pH of 6.9 to 7.5, and an electrical conductivity of 90 to 130 μS / cm for 1 minute is less than the chloride ion concentration of the raw water.
[0015] Another aspect of the present invention relates to an adsorbent for purifying plating liquid, which is formed by activated carbon, and the iodine adsorption per unit mass is 1000-1400 mg / g, the ash content of the activated carbon is less than 0.5 mass%, and the chloride content of the activated carbon is less than 0.0030 mass%. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a perspective view of a template for producing a molded body of the plating solution purification filter according to the present embodiment.
[0017] Figure 2 It means use Figure 1 A three-dimensional view of an example of a molded body according to this embodiment obtained by using a template.
[0018] Figure 3 This is a diagram for explaining a method of cutting out a sample when measuring the specific surface area of activated carbon in a molded body. DETAILED DESCRIPTION
[0019] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to these descriptions.
[0020] (Filter for plating solution purification)
[0021] The filter for plating liquid purification of the present embodiment comprises an adsorbent formed by activated carbon, and has a molded body with an iodine adsorption amount per unit mass of 930 to 1300 mg / g. The chloride ion concentration of filtered water obtained after filtering raw water having a chloride ion concentration of 6.0 to 9.0 mg / L, a pH of 6.9 to 7.5, and a conductivity of 90 to 130 μS / cm for 1 minute is less than the chloride ion concentration of the raw water.
[0022] By having such a configuration, it is possible to efficiently remove decomposition products generated from the additive from the plating solution while suppressing the removal of the additive, and it is possible to suppress the elution of chlorine into the plating solution.
[0023] This is presumably because by setting a lower limit to the iodine adsorption amount per unit mass of the molded body, the performance of removing decomposition products generated by the additive from the plating solution can be ensured, and by setting an upper limit to the iodine adsorption amount, the removal of the additive from the plating solution can be suppressed.
[0024] Furthermore, it is considered that by setting the chloride ion concentration of filtered water obtained by filtering raw water using the plating solution purification filter of the present embodiment to a predetermined value or less, chlorine elution into the plating solution can be suppressed.
[0025] The iodine adsorption per unit mass of the molded body contained in the filter for purifying the plating solution of the present embodiment (hereinafter sometimes referred to as "molded body iodine adsorption") is 930 to 1300 mg / g. If the iodine adsorption of the molded body is less than 930 mg / g, the decomposition products cannot be fully removed from the plating solution, which has an adverse effect on the formed plating layer. On the other hand, if the iodine adsorption of the molded body is more than 1300 mg / g, not only the decomposition products but also the additives are removed from the plating solution, and the plating layer cannot be fully formed. The iodine adsorption of the molded body is preferably 940 mg / g or more, and more preferably 950 mg / g or more. Moreover, the iodine adsorption of the molded body is preferably 1290 mg / g or less, and more preferably 1200 mg / g or less. In the present embodiment, the iodine adsorption of the molded body is measured and calculated according to the method for obtaining the "iodine adsorption performance" specified in JIS K 1474:2014 (test method for activated carbon) as described in the examples described later.
[0026] With regard to the filter for plating solution purification of the present embodiment, the chloride ion concentration of the filtered water (hereinafter sometimes referred to as "filtered water") obtained after filtering the raw water for 1 minute using the filter is less than the chloride ion concentration of the raw water. In the case where the chloride ion concentration of the filtered water is higher than the chloride ion concentration of the raw water, chlorine is dissolved into the plating solution after the decomposition products are removed by filtration, causing an adverse effect on the formed plating layer. However, according to the filter for plating solution purification of the present embodiment, the adverse effect of chlorine on the plating layer can be suppressed. The difference between the chloride ion concentration of the filtered water and the chloride ion concentration of the raw water (the value of subtracting the chloride ion concentration of the raw water from the chloride ion concentration of the filtered water) is preferably less than -0.5 mg / L. In the present embodiment, the chloride ion concentrations of the raw water and the filtered water are measured by the ion chromatography method described in the examples described later.
[0027] Here, the reason why the chloride ion concentration of the filtered water becomes higher than the chloride ion concentration of the raw water can be cited as chlorine or chloride (hereinafter referred to as "chlorine, etc.") contained in the activated carbon constituting the molded body. Activated carbon, especially activated carbon made from plant-based carbonaceous materials such as coconut shells, contains a certain amount of chlorine, etc. as impurities. The chlorine, etc. contained in the activated carbon can be reduced by further heat treatment after washing the activated activated carbon with an acid in order to reduce impurities other than chlorine, etc. However, in the case where the activated carbon contains chlorine, etc. that exceeds its adsorption performance, the chloride ion concentration of the filtered water is sometimes higher than the chloride ion concentration of the raw water.
[0028] In the case of the filter for plating solution purification of the present embodiment, the conductivity of the filtered water obtained after filtering the raw water for 1 minute using the filter is preferably less than the value obtained by adding 5μS / cm to the conductivity of the raw water (the value obtained by subtracting the conductivity of the raw water from the conductivity of the filtered water is less than 5μS / cm). The conductivity of the filtered water increases due to the metal components and impurities such as chlorine dissolved from the molded body. In the case where the conductivity of the filtered water is high and exceeds the value obtained by adding 5μS / cm to the conductivity of the raw water, the eluted metal components and chlorine from the activated carbon are dissolved into the plating solution after the decomposition products are removed by filtration, sometimes causing adverse effects on the formed plating layer. The difference between the conductivity of the filtered water and the conductivity of the raw water (the value obtained by subtracting the conductivity of the raw water from the conductivity of the filtered water) is preferably less than 3μS / cm, and more preferably less than 1μS / cm. The lower limit of the conductivity of the filtered water is not particularly limited, but if the conductivity is excessively reduced, the cost of the molded body becomes too high. Therefore, the difference between the conductivity of the filtered water and the conductivity of the raw water is preferably -7 μS / cm or more, and more preferably -6 μS / cm or more. In the present embodiment, the conductivity of the raw water and the filtered water is measured using a pH meter "F-74" and a ToupH electrode "9615S-10D" (both manufactured by HORIBA Advanced Technologies Co., Ltd.).
[0029] Here, the raw water used for the evaluation of the chloride ion concentration and the evaluation of the conductivity has a chloride ion concentration of 6.0 to 9.0 mg / L, a pH of 6.9 to 7.5, and a conductivity of 90 to 130 μS / cm. The raw water can be purified water obtained by filtering tap water with activated carbon. The chloride ion concentration, pH, and conductivity of the purified water are measured. As long as any item is within the range, it can be directly used as raw water for evaluation. When the chloride ion concentration of the purified water is lower than the range, it can be increased by adding sodium chloride (NaCl). When the chloride ion concentration of the purified water is higher than the range, it can be reduced by adding ion exchange water. When the conductivity of the purified water is lower than the range, it can be reduced by adding sodium sulfate (Na 2 SO 4) to increase it, and when the conductivity of the purified water is higher than the above range, it can be reduced by adding ion exchange water. As the activated carbon for purifying water used to adjust the raw water, a commercial product can be used.
[0030] The plating solution purification filter of the present embodiment preferably has a methylene blue cyclic adsorption number of more than 4 times and less than 12 times. As described in the embodiment described later, 2L of a methylene blue aqueous solution with an initial concentration of about 120mg / L is circulated in the plating solution purification filter, and if the concentration of the methylene blue aqueous solution 30 minutes after the start of circulation is less than 2mg / L, methylene blue is added in a manner to the initial concentration and the circulation is continued, and this operation is repeated until the concentration of the methylene blue aqueous solution 30 minutes after the addition of methylene blue exceeds 2mg / L, at which time the number of repetitions (the value obtained by adding 1 to the number of times methylene blue is added) is the number of methylene blue cyclic adsorptions.
[0031] If the number of cycles of methylene blue is less than 4 times, the decomposition products cannot be fully removed from the plating solution, which adversely affects the formed coating. On the other hand, if the number of cycles of methylene blue is more than 12 times, not only the decomposition products, but also the additives are removed from the plating solution, and the coating cannot be fully formed. The number of cycles of methylene blue is preferably more than 5 times, more preferably more than 6 times. Moreover, the number of cycles of methylene blue is preferably less than 11 times, more preferably less than 10 times. In the present embodiment, the number of cycles of methylene blue is measured by the method described in the embodiments described below.
[0032] In the case of the filter for plating liquid purification of the present embodiment, the percentage of the pore volume of the activated carbon having a diameter of 1.0 nm or more and 1.5 nm or less measured by the MP method (hereinafter referred to as "1 nm pore volume percentage") is preferably 2.3% or more relative to the total pore volume of the activated carbon measured by setting the pore volume calculation relative pressure to 0.990. If the 1 nm pore volume percentage is lower than 2.3%, the decomposition products cannot be fully removed from the plating liquid, which has an adverse effect on the formed plating layer. The 1 nm pore volume percentage is preferably 2.8% or more, and more preferably 3.0% or more. In the present embodiment, the 1 nm pore volume percentage is measured by the method described in the examples described later.
[0033] With regard to the filter for purifying the plating solution of the present embodiment, the average pore size of the activated carbon measured by the MP method is preferably greater than 1.70 nm and less than 1.92 nm. If the average pore size of the activated carbon is less than 1.70 nm, the decomposition products cannot be fully removed from the plating solution, which has an adverse effect on the formed plating layer. On the other hand, if the average pore size of the activated carbon is large and exceeds 1.92 nm, not only the decomposition products, but also the additives are removed from the plating solution, and the plating layer cannot be fully formed. The average pore size of the activated carbon is preferably greater than 1.71 nm, and more preferably greater than 1.74 nm. In addition, the average pore size of the activated carbon is preferably less than 1.91 nm, and more preferably less than 1.88 nm. In the present embodiment, the average pore size of the activated carbon is measured by the method described in the examples described later.
[0034] (Activated carbon)
[0035] The activated carbon used as an adsorbent in the molded body of the plating solution purification filter of this embodiment preferably has an iodine adsorption amount per unit mass of 1000 to 1400 mg / g, an ash content of 0.5 mass % or less, and a chloride content of 0.0030 mass % or less.
[0036] If the iodine adsorption per unit mass of the activated carbon (hereinafter sometimes referred to as "activated carbon iodine adsorption") is less than 1000 mg / g, even if a filter for purifying the plating solution made using the activated carbon is used, the decomposition products cannot be fully removed from the plating solution, which has an adverse effect on the formed plating layer. On the other hand, if the iodine adsorption of the activated carbon is more than 1400 mg / g, not only the decomposition products but also the additives are removed from the plating solution by using a filter for purifying the plating solution made using the activated carbon, and the plating layer cannot be fully formed. The iodine adsorption of the activated carbon is preferably greater than 1050 mg / g, and more preferably greater than 1060 mg / g. Moreover, the iodine adsorption of the activated carbon is preferably less than 1390 mg / g, and more preferably less than 1380 mg / g. In this embodiment, the iodine adsorption of the activated carbon is measured and calculated by the same method as the iodine adsorption of the molded body.
[0037] If the ash content of the activated carbon exceeds 0.5% by mass, ash will be eluted in the plating solution filtered by the plating solution purification filter made using the activated carbon, which will have an adverse effect on the formed plating layer. In order to suppress the ash from being eluted into the plating solution, the ash content of the adsorbent is preferably 0.4% by mass or less, more preferably 0.3% by mass or less.
[0038] If the chloride content of the activated carbon exceeds 0.0030 mass %, chloride will be eluted in the plating solution filtered by the plating solution purification filter made using the activated carbon, which will have an adverse effect on the formed plating layer. In order to suppress the elution of chloride into the plating solution, the chloride content of the activated carbon is preferably 0.0029 mass % or less, and more preferably 0.0020 mass % or less.
[0039] The activated carbon used in the present embodiment may be obtained by, for example, subjecting a carbonaceous material to at least one of carbonization and activation.
[0040] When carbonization of carbonaceous materials is required, oxygen or air can usually be isolated and carried out at, for example, 400 to 800°C, preferably 500 to 800°C, and more preferably 550 to 750°C. As an activation method, any one of gas activation and chemical reagent activation methods can be adopted, or the gas activation method and chemical reagent activation method can be combined, and the gas activation method with less impurity residue is particularly preferred. The gas activation method can be carried out by reacting the carbonized carbonaceous material with an activation gas (such as water vapor, carbon dioxide gas, etc.) at, for example, 750 to 1100°C, preferably 800 to 980°C, and more preferably 850 to 950°C. Considering the safety of the operation and the reactivity of the carbonaceous material, the activation gas is preferably a water vapor-containing gas containing 10 to 40% by volume of water vapor. The activation time and the heating rate are not particularly limited and can be appropriately selected according to the type, shape, and size of the selected carbonaceous material.
[0041] Carbonaceous materials are not particularly limited, and examples thereof include: plant-based carbonaceous materials (e.g., wood, wood shavings, charcoal, fruit shells such as coconut shells and walnut shells, fruit seeds, byproducts of pulp manufacturing, lignin, waste molasses and other plant-based materials); mineral-based carbonaceous materials (e.g., peat, lignite, brown coal, bituminous coal, anthracite, coke, coal tar, coal tar, petroleum distillation residues, petroleum asphalt and other mineral-based materials); synthetic resin-based carbonaceous materials (e.g., phenolic resins, polyvinylidene chloride, acrylic resins and other synthetic resin-based materials); natural fiber-based carbonaceous materials (e.g., natural fibers such as cellulose, natural fiber-based materials such as regenerated fibers such as rayon) and the like. These carbonaceous materials can be used alone or in combination of two or more. From the viewpoint of obtaining a molded body having the characteristics described above, coconut shells and phenolic resins among these carbonaceous materials are preferred, and coconut shells are more preferred.
[0042] In particular, when using plant-based carbonaceous materials such as coconut shells or mineral-based carbonaceous materials, the activated carbon may be washed to remove ash or chemical reagents. Acid is used for washing, and hydrochloric acid with high washing efficiency is preferred. After acid washing, the acid is fully rinsed with water.
[0043] The shape of the activated carbon of this embodiment may be any shape such as powder, particle, fiber (filament, woven (cloth), felt), etc., and can be appropriately selected according to the application. Preferably, the activated carbon has a particle shape with high adsorption performance per unit volume.
[0044] The particle size of the activated carbon of the present embodiment is not particularly limited, and the 50% particle size (D50) in the cumulative particle size distribution based on volume is preferably about 120 to 170 μm, more preferably about 125 to 165 μm, and further preferably about 130 to 160 μm. As long as the particle size of the activated carbon is within this range, it is easy to obtain a molded body that can both inhibit the removal of the additive and efficiently remove the decomposition products produced by the additive from the plating solution. In the present embodiment, the numerical value of the D50 is a value measured by a laser diffraction and scattering method, and can be measured using, for example, a wet particle size distribution measuring device (Microtrac MT3300EX II) manufactured by Nikkiso Co., Ltd.
[0045] (Binder)
[0046] The molded body of this embodiment preferably contains a fibrous binder. As a fibrous binder, as long as it can be wrapped around activated carbon to be shaped, can be mixed with activated carbon after acid washing and has acid resistance so that the filter can be used in an acidic plating solution, it is not particularly limited, and both synthetic and natural products can be widely used. As such a binder, for example, acrylic fiber, polyethylene fiber, polypropylene fiber, polyacrylonitrile fiber, cellulose fiber, nylon fiber, aramid fiber, pulp, etc. can be listed. The fiber length of the fibrous binder is preferably less than 4 mm.
[0047] These fibrous binders can be used in combination of two or more. It is particularly preferred to use polyacrylonitrile fiber or cellulose pulp as the binder. This can further increase the density and strength of the molded body and inhibit performance degradation.
[0048] In the present embodiment, the water permeability of the fibrous polymer binder is about 10 to 150 mL in terms of CSF value. In the present embodiment, the CSF value is a value measured in accordance with JIS P 8121-2:2012 (Pulp - Freeness Test Method - Part 2: Canadian Standard Freeness Method). In addition, the CSF value can be adjusted, for example, by fibrillating the binder.
[0049] If the CSF value of the fibrous polymer binder is less than 10 mL, liquid permeability cannot be obtained and the pressure loss may also increase. On the other hand, when the CSF value exceeds 150 mL, the powdered activated carbon cannot be fully retained, the strength of the molded body is reduced, and there is a possibility that the adsorption performance will deteriorate.
[0050] From the viewpoints of the adsorption effect of the decomposition products in the plating solution, moldability, etc., the mixing ratio of the activated carbon and the fibrous binder in the molded body of the present embodiment is preferably about 4.0-6.0 parts by mass of the fibrous binder relative to 100 parts by mass of the activated carbon. If the amount of the fibrous binder is less than 4.0 parts by mass, it is possible that sufficient strength cannot be obtained and the molded body cannot be molded. In addition, if the amount of the fibrous binder exceeds 6.0 parts by mass, the adsorption performance may decrease. It is more preferable to mix 4.5 to 5.5 parts by mass of the fibrous binder.
[0051] (Modification of the filter for plating solution purification)
[0052] The filter for plating liquid purification of this embodiment may be a cylindrical filter having a core in addition to the molded body. By setting it to a cylindrical shape, there is an advantage that the flow resistance can be reduced.
[0053] The core that can be used in this embodiment is not particularly limited as long as it can be inserted into the hollow part of a cylindrical molded body to reinforce the molded body, and is preferably a trical pipe, a net drain pipe, a ceramic filter, or a cylindrical nonwoven fabric laminated tube. In addition, a nonwoven fabric may be wrapped around the outer periphery of the core.
[0054] Furthermore, the filter for purifying the plating solution of the present embodiment may include a nonwoven fabric wound around the outer periphery of the cylindrical molded body, or may include gaskets bonded to both side end surfaces of the molded body.
[0055] (How to use the filter for plating solution purification)
[0056] The plating solution purification filter of this embodiment is immersed in a plating solution tank containing a plating solution and used. By circulating the plating solution through the filter, the removal of additives in the plating solution can be suppressed and decomposition products generated by the additives can be adsorbed and removed.
[0057] (Method for producing molded article)
[0058] The molded body included in the filter for purifying a plating solution of the present embodiment can be produced by any method without particular limitation. From the viewpoint of efficient production, a slurry suction method is preferred.
[0059] Hereinafter, the details of the method for producing a cylindrical molded body according to the present embodiment will be described as an example thereof, but the present invention is not limited thereto.
[0060] Specifically, for example, a cylindrical molded body can be obtained by a manufacturing method comprising the following steps: a slurry preparation step, in which powdered activated carbon and a fibrous binder are dispersed in water to prepare a slurry; a filtration step, in which the slurry is filtered while being sucked to obtain a preform; a drying step, in which the preform is dried to obtain a dried molded body; and a grinding step, in which the outer surface of the molded body is ground as needed.
[0061] (Slurry preparation process)
[0062] In the present embodiment, in the slurry preparation process, for example, a slurry in which powdered activated carbon and a fibrous binder are dispersed in a solvent is prepared in such a manner that the fibrous binder is 4.5 to 5.5 parts by mass relative to 100 parts by mass of activated carbon, and the solid content concentration is 4.0 to 6.0% by mass (particularly preferably 4.5 to 5.5% by mass). The solvent is not particularly limited, and water or the like is preferably used. If the solid content concentration of the slurry is too high, there is a problem that the dispersion tends to become uneven and spots are easily generated in the molded body. On the other hand, if the solid content concentration is too low, not only the molding time becomes longer, thereby reducing productivity, but also the density of the molded body becomes higher, thereby easily clogging due to capturing turbid components.
[0063] (Filtration process)
[0064] Next, in the suction filtration step, for example, Figure 1 The cylindrical molding template 1 shown in the figure, which has a plurality of suction holes 3 on the surface of the core body 2 and flanges 4, 4' installed at both ends, is installed with the above-mentioned center core and immersed in the slurry contained in the container, and the slurry is filtered while being sucked from the inner side of the template 1 through the filtrate discharge port 5, so that the slurry is attached to the template 1. As a suction method, a common method can be used, such as a method of suction using a suction pump, etc. The preform 7 is compressed to a specified diameter in a state of being attached to the template 1.
[0065] (Drying process)
[0066] After the preform 7 is formed by the suction filtration step, the flanges 4 and 4' at both ends of the template 1 are removed and the core 2 is pulled out, thereby obtaining a preform 7 in a hollow cylindrical shape. In the drying step, the preform 7 removed from the template 1 is dried using a dryer or the like, thereby obtaining a Figure 2 The molded body 6 shown (the molded body of this embodiment).
[0067] The drying temperature is, for example, about 100 to 150° C. (especially 110 to 130° C.), and the drying time is, for example, about 4 to 24 hours (especially 8 to 16 hours). If the drying temperature is too high, the fibrous binder is deteriorated or melted, which may easily reduce the filtering performance or the strength of the molded body 6. If the drying temperature is too low, there is a risk that the drying time becomes longer or the drying becomes insufficient.
[0068] (Grinding process)
[0069] If necessary, a grinding process may be performed after the drying process to further adjust the outer diameter of the filter or reduce the unevenness of the outer peripheral surface. The grinding method used in this embodiment is not particularly limited as long as the outer surface of the dried molded body 6 can be ground (or polished). A commonly used grinding method may be used, but from the perspective of grinding uniformity, a method using a grinder that rotates the molded body 6 itself for grinding is preferred.
[0070] The grinding process is not limited to the method using a grinder, and for example, a fixed flat grindstone may be used to grind the molded body 6 fixed to the rotating shaft. In this method, the generated grinding chips are easily accumulated on the grinding surface, so it is more effective to perform grinding while blowing air.
[0071] The molded body thus obtained can be used as a filter for plating solution purification of the present embodiment. For example, after the molded body is manufactured by the manufacturing method described above, it can be cut into a desired size and shape according to the amount of plating solution to be treated, thereby obtaining a filter for plating solution purification. Further, as required, a core can be inserted into the hollow part of the molded body, a cover can be installed at the distal end of the molded body, or a nonwoven fabric can be wrapped around the periphery of the molded body.
[0072] (Adsorbent for plating solution purification)
[0073] Another embodiment of the present invention is an adsorbent for plating solution purification composed of activated carbon, wherein the iodine adsorption per unit mass is 1000 to 1400 mg / g, the ash content of the activated carbon is 0.5% by mass or less, and the chloride content of the activated carbon is 0.0030% by mass or less. The reasons for specifying the iodine adsorption, ash content, and chloride content are the same as those for specifying these items of the activated carbon.
[0074] By using the plating solution purification adsorbent of this embodiment, the removal of additives can be suppressed and the decomposition products generated by the additives can be efficiently removed from the plating solution, and the leaching of chlorine and ash into the plating solution can be suppressed. The plating solution purification adsorbent of this embodiment can be used in the plating solution purification filter.
[0075] As described above, this specification discloses the techniques of various embodiments, and the main techniques are summarized as follows.
[0076] A filter for purifying a plating solution according to one aspect of the present invention comprises a molded body containing an adsorbent formed of activated carbon and having an iodine adsorption amount per unit mass of 930 to 1300 mg / g, wherein the chloride ion concentration of filtered water obtained after filtering raw water having a chloride ion concentration of 6.0 to 9.0 mg / L, a pH of 6.9 to 7.5, and an electrical conductivity of 90 to 130 μS / cm for 1 minute is less than the chloride ion concentration of the raw water.
[0077] With such a configuration, it is possible to provide a filter for purifying a plating solution that can efficiently remove decomposition products generated from the additive from the plating solution while suppressing removal of the additive, and can suppress elution of chlorine into the plating solution.
[0078] In the plating solution purification filter, the conductivity of the filtered water may be equal to or lower than the conductivity of the raw water plus 5 μS / cm. This can suppress the dissolution of metal components into the plating solution and form a high-quality plating layer.
[0079] In the filter for purifying the plating solution, the molded body may contain a fibrous binder, whereby the shape of the molded body is not easily deformed, the removal of the additive can be stably suppressed for a long period of time, and decomposition products generated by the additive can be efficiently removed from the plating solution.
[0080] In the filter for purifying the plating solution, the activated carbon may be made of coconut shells, thereby making it possible to manufacture the filter for purifying the plating solution at low cost.
[0081] In the filter for purifying the plating solution, the number of cycles of adsorption of methylene blue may be 4 or more and 12 or less. This can suppress the removal of the additive and efficiently remove the decomposition products generated by the additive from the plating solution.
[0082] In the filter for purifying the plating solution, the percentage of the volume of pores of the activated carbon having a diameter of 1.0 nm or more and 1.5 nm or less measured by the MP method may be 2.3% or more relative to the total volume of the activated carbon pores measured by setting the relative pressure for calculating the pore volume to 0.990. This can suppress the removal of the additive and efficiently remove the decomposition products generated by the additive from the plating solution.
[0083] In the plating solution purification filter, the average pore size of the activated carbon measured by the MP method may be 1.70 nm to 1.92 nm, thereby suppressing the removal of the additive and efficiently removing decomposition products generated by the additive from the plating solution.
[0084] Another aspect of the present invention relates to an adsorbent for purifying plating liquid, which is formed by activated carbon, and the iodine adsorption per unit mass is 1000-1400 mg / g, the ash content of the activated carbon is less than 0.5 mass%, and the chloride content of the activated carbon is less than 0.0030 mass%.
[0085] According to such a configuration, an adsorbent for plating solution purification can be provided for obtaining a plating solution purification filter that can suppress removal of additives, efficiently remove decomposition products generated by the additives from the plating solution, and suppress elution of chlorine into the plating solution.
[0086] Example
[0087] The present invention is described in more detail below based on examples, but these examples do not limit the present invention in any way.
[0088] First, the production methods of the activated carbon, the molded body, and the filter prepared in each of the Examples shown in Tables 1 to 3 are described.
[0089] [Material for Molded Article]
[0090] (Granular activated carbon)
[0091] The raw material of granular activated carbons 1 to 11 is coconut shell. The coconut shell carbon carbonized at 400° C. to 600° C. is activated by steam at 900° C. to 950° C. The activation time is adjusted so as to achieve the target iodine adsorption amount. The activated carbon is used as granular activated carbon 11.
[0092] The activated carbon was washed with dilute hydrochloric acid, then washed with ion-exchanged water, and dried at 120° C. to obtain granular activated carbon. The washed and dried activated carbons were designated as granular activated carbons 7 to 9.
[0093] The washed and dried activated carbon was further heat-treated in LPG combustion gas at a heat-treatment temperature of 700° C. and a water vapor partial pressure of about 40%. The heat-treated activated carbon was designated as granular activated carbons 1 to 6 and 10.
[0094] (Fiber-like activated carbon)
[0095] The raw material of the fibrous activated carbon 1 is phenol resin. Phenolic resin fibers ("KT-2800" manufactured by Gunei Chemical Industry Co., Ltd.) were heat-treated in LPG combustion gas at 980°C to obtain fibrous activated carbon 1 (2 denier, 800,000 fibers).
[0096] (Fiber-like binder)
[0097] As the fibrous binder, "Fibrillated acrylic pulp Bi-PUL / F" manufactured by Nippon Exlan Industries, Ltd. was used.
[0098] [Manufacturing of Molded Article]
[0099] (Using granular activated carbon slurry)
[0100] Granular activated carbons 1 to 10 were pulverized with a ball mill and then classified with a JIS standard sieve having an upper mesh of 80 and a lower mesh of 325 to obtain powdered activated carbons having a particle size (D50) shown in Table 2.
[0101] 0.11 kg (CSF=55 mL) of the fibrous binder was added in terms of solid content to 2.0 kg of the powdered activated carbon, and the mixture was stirred and dispersed in tap water to prepare 30 L of slurry.
[0102] (Using slurry of fibrous activated carbon)
[0103] 1 kg of fibrous activated carbon 1 was added to 0.055 kg (CSF = 55 mL) of the fibrous binder and 100 L of tap water in terms of solid content, and put into a small beater to beat the slurry in such a way that the density of the molded body for beating density measurement becomes 0.22 g / mL.
[0104] The density of the shaped body for measuring the beating density prepared from the slurry after beating is measured as follows. Figure 1 The center axis (core) of a mold (template) with an outer diameter of 40 mm and an outer diameter flange spacing of 50 mm and a plurality of suction holes (diameter 3 mm, spacing 5 mm) of the shape shown was wrapped with a 300-mesh metal mesh to make an outer diameter of 18 mm. The slurry was sucked by the mold to produce a cylindrical molded body for measuring beating density, and the density (beating density) of the molded body was calculated from the weight and size after drying.
[0105] (Molding of slurry)
[0106] Use Figure 1 A mold (template) of the shape shown, having an outer diameter of 63 mm, a center axis (core body) diameter of 30 mm, and a length between flanges of 245 mm, with multiple small holes for suction, is installed with a center axis filter (MF filter manufactured by Asahi Textile Industry Co., Ltd., with a nominal pore diameter of 30 μm, an inner diameter of 30 mm, an outer diameter of 33 mm, and a length of 245 mm) to suck the obtained slurry, and suction is performed until the outer diameter of the preform formed by the sucked slurry is about 65 mm, which is about 2 mm larger than the outer diameter of the mold.
[0107] Then, the obtained preform is rotated while being pressed with a plate for compression molding (rotation molding) until it becomes the same outer diameter as the mold, removed from the mold and dried, thereby completing the process as shown in FIG. Figure 2 The cylindrical molded body shown. A layer of nonwoven fabric (spunbonded nonwoven fabric "ELEVEST0703WDO" manufactured by Unitika Co., Ltd.) was wrapped around the periphery of the completed molded body, and gaskets punched from a 2mm thick foamed polyethylene sheet in a donut shape with an outer diameter of 63mm and an inner diameter of 30mm were bonded to both ends of the molded body with a 0.5mm thick hot melt adhesive, and the length was adjusted to 250mm, thereby completing the filter for plating liquid purification. The parts or filters processed from the molded body were used in Test No. 1 to 12.
[0108] Next, the evaluation method of the activated carbon and the molded body prepared in each example shown in Table 1 to Table 3, and the evaluation method of the filtered water filtered in each example are described.
[0109] [Ash and chloride content in activated carbon, iodine adsorption capacity of activated carbon]
[0110] For activated carbon before mixing with a binder, the following conditions shall be followed: The iodine adsorption amount (activated carbon iodine adsorption amount) was measured by the determination method of JIS. The ash content and chloride content in the activated carbon were also measured according to the method specified in JIS.
[0111] [Determination of metal (Na, K) content in activated carbon]
[0112] 10 mL of concentrated nitric acid (1.38) was added to 0.1 g of an activated carbon sample before mixing with a binder, and microwaves were applied using a parallel amplified microwave synthesis device ("Microwave MARS6" manufactured by CEM) to prepare an activated carbon decomposition liquid.
[0113] The element contents in the decomposition liquid were measured using a multi-element simultaneous analysis ICP emission spectrophotometer ("ICPE-9820" manufactured by Shimadzu Corporation). Based on the obtained element contents, the element contents in the activated carbon were calculated. The contents of Na and K shown in Table 1 are the values per 1 kg of activated carbon calculated as described above.
[0114] [Particle size determination of activated carbon]
[0115] The particle size (D50) of each activated carbon after being crushed by a ball mill was measured by the laser diffraction measurement method described below. That is, the activated carbon to be measured was added to ion exchange water together with a surfactant, ultrasonic vibration was applied to prepare a uniform dispersion, and the particle size distribution was measured using a particle size distribution measuring device ("Microtrac MT3300EX-II" manufactured by Microtrac BEL). As a surfactant, "Polyoxyethylene (10) octylphenyl ether" manufactured by Wako Pure Chemical Industries, Ltd. was used. The analysis conditions are shown below.
[0116] (Analysis conditions)
[0117] Number of measurements: Average value of 3 times
[0118] Measurement time: 30 seconds
[0119] Distribution Display: Volume
[0120] Particle size classification: Standard
[0121] Calculation mode: MT3000II
[0122] Solvent name: Water
[0123] Measurement upper limit: 2000μm, measurement lower limit: 0.021μm
[0124] Residual component ratio: 0.00
[0125] By composition ratio: 0.00
[0126] Residual component ratio setting: Invalid
[0127] Particle permeability: Absorption
[0128] Particle Refractive Index: Not Applicable (N / A)
[0129] Particle shape: Not applicable (N / A)
[0130] Solvent refractive index: 1.333
[0131] DV value: 0.0882
[0132] Transmittance (TR): 0.800~0.930
[0133] Dilation filter: invalid
[0134] Flow rate: 70%
[0135] Ultrasonic output: 40W
[0136] Ultrasonic time: 180 seconds
[0137] [Measurement of specific surface area, pore volume and average pore diameter of activated carbon in molded body]
[0138] The molded body before the peripheral nonwoven fabric and the gasket are installed is randomly placed at a position 115 mm from the end surface in the length direction. Figure 3 The sample was cut with a cutter in a volume of about 6 mL as shown. The cut sample was placed in a crucible, heated at 700°C for 1 hour in a nitrogen atmosphere, and then cooled to room temperature in a nitrogen atmosphere to be used as a sample for measuring the specific surface area and pore volume. The specific surface area and pore volume of the activated carbon in the molded body were calculated using the following method using this sample.
[0139] Specific surface area S1(m 2 The nitrogen adsorption isotherm at 77 K was measured using a high-precision fully automatic gas adsorption apparatus ("BELSORP-mini" manufactured by Microchip Bayer), and the nitrogen adsorption isotherm was determined by the BET method.
[0140] The total pore volume V1 (mL / g) is calculated based on the amount of nitrogen adsorption using the high-precision fully automatic gas adsorption device. Specifically, the amount of nitrogen adsorption (V) at a relative pressure of 0.990 is calculated using the pore volume measured using the high-precision fully automatic gas adsorption device, and converted into the volume of liquid nitrogen (Vp) using the following formula (1). The obtained Vp value is used as the total pore volume V1 (mL / g). In formula (1), Mg is the molecular weight (28.013) of the adsorbate (nitrogen), ρg (g / cm 3 ) is the density of the adsorbate (nitrogen) (0.808 g / cm 3 ).
[0141] Vp=V×Mg / (22414×ρg) (1)
[0142] The average pore diameter D1 (nm) is calculated by assuming that the pores are cylindrical and using the total pore volume V1 (mL / g) and specific surface area S1 (m 2 / g) and was determined by the following formula (2).
[0143] D1=(V1 / S1)×4×1000 (2)
[0144] The nitrogen adsorption isotherm was analyzed by the MP method, and the total pore volume (mL / g) of pores in the range of 1.0 to 1.5 nm in diameter was calculated. NGCB-BEL.t was used as the reference curve.
[0145] [Iodine adsorption of molded body]
[0146] The sample was cut at the same position and size as the sample used in the measurement of the specific surface area of the activated carbon in the molded body. The cut sample was cut into sample pieces of different and arbitrary sizes and dried at 115°C for 3 hours. After drying, the weight of the sample cooled in the dryer was measured, and each sample piece was crushed with a spatula to eliminate lumps, and used as a sample for measuring the iodine adsorption amount of the molded body. Using these samples, the iodine adsorption amount of the molded body was measured according to the measurement method of "iodine adsorption performance" specified in JIS K 1474:2014 (Test method for activated carbon).
[0147] [Methylene blue (MB) cycle number]
[0148] The cylindrical molded body wrapped with nonwoven fabric was cut into a thickness of 16.3 mm, and gaskets were bonded to both ends by hot melting to serve as a sample filter for MB cycle number determination. The gasket used a donut-shaped gasket with an outer diameter of 63 mm and an inner diameter of 30 mm punched out of a 2 mm thick foamed polyethylene sheet. The aqueous solution (MB aqueous solution) for MB cycle number determination used an aqueous solution in which methylene blue (MB) was added to ion exchange water in a concentration of about 120 mg / L. As a column for setting the sample filter, a homemade column with an inner diameter of 70 mm was used, and its structure adopted a structure that can seal both ends of the sample filter with ribs.
[0149] A sample filter was set on the column, and 2L of MB aqueous solution was circulated from the outside to the inside of the sample at 20°C and a flow rate of 0.56L / min. If the MB concentration in the MB aqueous solution was below 2mg / L 30 minutes after the start of circulation, MB was further added to make the concentration about 120mg / L. This operation was repeated until the MB concentration exceeded 2mg / L 30 minutes after the addition of MB. The number of repetitions (the value obtained by adding 1 to the number of MB additions) until the MB concentration exceeded 2ppm 30 minutes after the start of circulation or the addition of MB was taken as the number of MB cycles.
[0150] The pump used for the circulation was "Digital Pump 07522-20" manufactured by Yamato Scientific Co., Ltd. The concentration of MB in the MB aqueous solution was measured using an ultraviolet visible spectrophotometer ("UV-1800" manufactured by Shimadzu Corporation) at a wavelength of 665 nm by arbitrarily diluting the MB aqueous solution with ion exchange water.
[0151] [Raw water]
[0152] As the raw water for filtration, tap water was filtered with activated carbon for water purification and the water temperature was adjusted to 20±3° C. The pH of the raw water was 6.9 to 7.5. In addition, the chloride ion concentration and conductivity of the raw water used in each example are shown in Table 3.
[0153] [Determination of chloride ion concentration in raw water and filtered water]
[0154] A filter for purifying a plating solution having a molded body, a nonwoven fabric wound around the molded body, and gaskets bonded to both ends of the molded body was set on a plastic shell ("1PA" manufactured by Advantech Corporation), and raw water was circulated at a flow rate of 10 L / min. 100 ml of filtered water obtained by filtering the raw water began to flow out from the outlet of the plastic shell 1 minute later, and the chloride ion concentration was measured under the following conditions using an ion chromatograph ("INTEGRION" manufactured by Thermo Fisher Scientific). 100 ml of unfiltered raw water was also extracted, and the chloride ion concentration was measured in the same way. When the chloride ion concentration of the filtered water was less than the chloride ion concentration of the raw water, the chlorine dissolution was judged as "○" (permitted), and when the chloride ion concentration of the filtered water was higher than or less than the chloride ion concentration of the raw water, the chlorine dissolution was judged as "×" (unpermitted).
[0155] (Ion chromatography conditions)
[0156] Column: AS23 4×250mm and AS23 4×50mm
[0157] Suppressor: AERS 500 Carbonate 4mm
[0158] Eluent: 4.5M sodium carbonate + 0.8mM sodium bicarbonate solution (ultrapure water)
[0159] [Conductivity measurement of raw water and filtered water]
[0160] The conductivity of the filtered water and raw water extracted for the chloride ion concentration measurement was measured using a pH meter ("LAQUA F-74" and "ToupH electrode 9615S-10D" manufactured by Horiba Advanced Technologies Co., Ltd.).
[0161] [Polyethylene glycol (PEG) removal performance evaluation]
[0162] The PEG removal performance test is conducted to determine the performance of the filter in removing decomposition products from the plating solution. In the PEG removal performance test, the plating solution was replaced by ion exchange water, the additive (high molecular organic compound) added to the plating solution was replaced by polyethylene glycol 20,000 (PEG20000), and the decomposition products (low molecular organic compounds) generated by the additive in the plating solution were replaced by polyethylene glycol 400 (PEG400).
[0163] The PEG removal performance was evaluated using the same sample filter as that used for measuring the MB cycle number.
[0164] As the PEG aqueous solution, two aqueous solutions were used, in which PEG20000 or PEG400 was added to ion-exchanged water so that the TOC concentration became about 1,650 mg / L.
[0165] A sample filter was set on the column, and 5 L of PEG aqueous solution was circulated from the outside to the inside of the sample at 20°C and a flow rate of 0.5 L / min. The TOC concentration in the PEG aqueous solution was measured 3 hours after the start of the flow, and the removal rates of PEG20000 and PEG400 from the PEG aqueous solution before the start of the flow were calculated.
[0166] The filter for plating solution purification of the present invention preferably removes only decomposition products without removing additives as much as possible, so PEG20000 corresponding to the additive is considered qualified with a removal rate of 25% or less, and PEG400 corresponding to the decomposition product is considered qualified with a removal rate of 25% or more. The removal performance that satisfies both the removal rate of PEG20000 of 25% or less and the removal rate of PEG400 of 25% or more is judged as "○" (acceptable), and the removal performance other than this is judged as "×" (unacceptable).
[0167] The pump used for the circulation was "Digital Pump 07522-20" manufactured by Yamato Scientific Co., Ltd. The TOC concentration in the PEG aqueous solution was measured using a total organic carbon meter ("TOC-Lcsh ASI-L" manufactured by Shimadzu Corporation).
[0168] [Plating quality assessment]
[0169] The plating solution filtered through the plating purification filter was used to plate the nickel test piece with copper plating, and the quality was visually confirmed. The sample was judged as "○" if it was good enough to be used as a plated product, "Δ" if it was barely usable as a plated product, and "×" if it had color spots or uneven thickness and could not be used.
[0170] The measurement and evaluation results of the above items are shown in Tables 1 to 3. Table 1 shows the measurement and evaluation results of the activated carbon before crushing or beating. Table 2 shows the measurement and evaluation results of the filter and the activated carbon in the filter. Table 3 shows the measurement results of the raw water and the filtered water filtered by the filter, the performance evaluation of the filter, and the evaluation of the plating quality.
[0171]
[0172]
[0173]
[0174] (Inspection)
[0175] The plating solution purification filter of this embodiment (the present invention example) can not only suppress the removal of PEG20000 but also efficiently remove PEG400 from the PEG solution, and can suppress the dissolution of chlorine into the PEG solution, showing excellent removal performance. Moreover, when the plating solution filtered by the plating solution purification filter of this embodiment is used for plating processing, excellent quality results are obtained.
[0176] In contrast, the plating solution purification filter of the comparative example was inferior in removal performance or suppression of chlorine elution. In addition, when the plating solution filtered by the plating solution purification filter of the comparative example was used for plating processing, inferior results were obtained.
[0177] Through the above description, it can be confirmed that the filter for plating solution purification according to the present invention can not only suppress the removal of additives, but also efficiently remove the decomposition products generated by the additives from the plating solution, and can suppress the dissolution of chlorine into the plating solution. In addition, it can be confirmed that when the filter for plating solution purification according to the present invention is used, the quality of the obtained plated product is good, so it is useful as a filter for plating solution purification.
[0178] This application is based on Japanese patent application No. 2018-245928 filed on December 27, 2018, the contents of which are incorporated herein by reference.
[0179] In order to describe the present invention, the present invention is appropriately and fully described in the above description with reference to the drawings and through the embodiments, but it should be understood that those skilled in the art can easily change and / or improve the above embodiments. Therefore, as long as the changes or improvements implemented by those skilled in the art do not depart from the scope of the rights of the claims recorded in the claims, the changes or improvements are interpreted as being included in the scope of the rights of the claims.
[0180] Industrial Applicability
[0181] The present invention has broad industrial applicability in the technical field related to a filter for purifying a plating solution and an adsorbent for purifying a plating solution.
Claims
1. A filter for purifying a plating solution, wherein: A molded body comprising an adsorbent formed of activated carbon and having an iodine adsorption amount per unit mass of 930 to 1300 mg / g, The chloride ion concentration of filtered water obtained by filtering raw water having a chloride ion concentration of 6.0 to 9.0 mg / L, a pH of 6.9 to 7.5, and an electrical conductivity of 90 to 130 μS / cm for 1 minute is less than or equal to the chloride ion concentration of the raw water. The chloride content of the activated carbon is 0.0030 mass % or less, The average pore diameter of the activated carbon measured by the MP method is 1.70 nm or more and 1.92 nm or less.
2. The filter for purifying a plating solution according to claim 1, wherein: The electrical conductivity of the filtered water is not more than a value obtained by adding 5 μS / cm to the electrical conductivity of the raw water.
3. The filter for purifying a plating solution according to claim 1 or 2, wherein: The molded body contains a fibrous binder.
4. The filter for purifying a plating solution according to claim 1 or 2, wherein: The activated carbon is made from coconut shell.
5. The filter for purifying a plating solution according to claim 1 or 2, wherein: The number of cycles of adsorption of methylene blue is 4 or more and 12 or less.
6. The filter for purifying a plating solution according to claim 1 or 2, wherein: The percentage of the volume of pores having a diameter of 1.0 nm or more and 1.5 nm or less of the activated carbon measured by the MP method is 2.3% or more relative to the total pore volume of the activated carbon measured at a pore volume calculation relative pressure of 0.
990.
7. An adsorbent for purifying a plating solution, wherein: Made of activated carbon, The iodine adsorption per unit mass is 1000~1400mg / g. The ash content of the activated carbon is 0.5 mass % or less, the chloride content of the activated carbon is 0.0030 mass % or less, The average pore diameter of the activated carbon measured by the MP method is 1.70 nm or more and 1.92 nm or less.
Citation Information
Patent Citations
Plating apparatus and plating method
JP2005240108A
Filter for purification
JP2012061390A
Flexible color adjustment for dark Cr(III) platings
CN108290382A
Production of activated carbon and activated carbon raw material
JP1987052113A
Method and apparatus for highly purifying activated carbon
JP2008007387A